Biodiesel production using palm fatty acid distillate and rice husk silica supported NiSO4 as catalyst - Hindryawati, Noor; Widodo, Nanang Tri; Arief, Moh. Syaiful; Hiyahara, Irfan Ashari; Gaanty Pragas, Maniam (AIP Publishing, 2020)
As one of the promising feedstocks for the development of biodiesel, palm fatty acid distillate (PFAD) has weaknesses such as the high free fatty acid (FFA) and water content. In order to overcome the weaknesses, the NiSO4− rice husk silica (Ni-RHS) catalyst was used in PFAD esterification. The optimization result at 9 h reaction time and 100 °C showed the MeOH : oil molar ratio is 15:1 and 15 wt.% catalyst amount with 88% of methyl ester. The catalyst could maintain catalytic activity more than 80% in two cycles and it proves that the regeneration and reuse of the catalyst were feasible and handy.